Porous tantalum scaffolds: Fabrication, structure, properties, and orthopedic applications. (15th November 2021) - Gao, Hairui; Yang, Jingzhou; Jin, Xia; Qu, Xinhua; Zhang, Faqiang; Zhang, Dachen; Chen, Haishen; Wei, Huiling; Zhang, Shupei; Jia, Weitao; Yue, Bing; Li, Xiaopeng
Graphical abstract: Additive Manufacturing of bioactive tantalum porous structures. Highlights: We systematically overviewed the research progress of porous Ta bone scaffolds combining our innovative work. First discussion on the fabrication-structure-property relationship of porous Ta scaffolds. Additive manufacturing (AM) is a powerful technique for fabricating patient-specific and anatomy-matching porous Ta bone scaffolds. First original report on the pre-clinical large animal study of AM-fabricated trabecular Ta scaffolds. Future perspectives of porous Ta bone scaffolds are concluded. Abstract: Porous tantalum scaffolds have been developed and clinically utilized as superior implantable biomaterials for orthopedic applications owing to their exceptional corrosion resistance, biocompatibility, osteointegration, and osteoconductivity. Moreover, the biomimetic porous structure and mechanical properties of these scaffolds match those of human bone tissues. Over the past twenty years, the fabrication, structure and properties optimization, and application expansion of porous tantalum scaffolds have been advanced by emerging manufacturing technologies, characterization methodologies, and clinical utilization strategies. Combining our innovative work and over two hundred extant publications, we overview the fabrication, structure, properties, and orthopedic applications of porous tantalum bone scaffolds. Additive manufacturing has become a powerful and versatile technique for fabricating patient-specific and anatomy-matching porous tantalum bone implants with well-designed architectures. Additively manufactured tantalum scaffolds are deemed as new biomaterials for bone repair, as their microstructures and mechanical properties differ from those of bioimplants fabricated by traditional technologies. To understand the safety and effectiveness of these scaffolds for orthopedic applications, we must undertake basic scientific investigations, in vitro studies, pre-clinical studies, and clinical research. Biomechanical studies and porous structure design based on finite element analysis are additional hot topics in tantalum scaffold research.